Complete mitochondrial sequence of Auricularia heimuer, one of the most popular edible fungus in China. Issue 2 (3rd July 2019) - Fang, Ming; Yao, Fangjie; Lu, Lixin; Zhang, Youmin; Wang, Peng; Lu, Jia; Wang, Wei; Chen, Xue
Abstract: Auricularia heimuer is one of the most popular edible fungi in China. It has high economic and medicinal value. The complete mitochondrial genome of A. heimuer is 40586 bp. It contains 48 genes, including 25 protein-coding genes, 22 tRNA genes, and 1 gene coding RNase P RNA. The G + C content is 37.92%. The phylogenetic relationships were constructed on the Bayesian inference method. It showed that A. heimuer was in distance to other species of Russulales, Polyporales, and Agaricales. The complete genome sequence of A. heimuer will provide a useful resource for the genetic and systematics studies.